Analisis Strategi Bersaing Menggunakan SWOT Dan Quantitative Strategic Planning Matrix (QSPM) Di J&T Express Sumbawa - Pitri Handayani; Ismi Mashabai; Silvia Firda Utami; Nurul Hudaningsih (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
J&T Express Sumbawa began operations in 2016. Based on the results of a questionnaire containing 10 questions to 20 customers, it was found that JNE was the preferred choice of consumers when selecting a freight forwarding service. This indicates that consumer interest in choosing J&T Express Sumbawa for shipping services has decreased. The method used to design J&T Express Sumbawa's competitive strategy involved analyzing the internal and external environment through the determination of IFAS weights, EFAS, the IE matrix position, and the formulation of strategies using SWOT analysis. For prioritizing alternative strategies, QSPM was used. The results of the IFAS matrix calculation yielded a total score of 2.913, and the EFAS matrix calculation yielded a total score of 3.524. The strategy from the IE matrix is described as a growth and development strategy. The SWOT matrix strategy produced 11 alternatives: 2 SO strategies, 3 ST strategies, 3 WO strategies, and 3 WT strategies. The QSPM matrix strategy priority assessment yielded 3 main priorities: strategy 5 with a TAS score of 5.692, which involves implementing technology to improve service quality; strategy 2 with a TAS score of 5.594; and strategy 10 with a TAS score of 5.328